Delivering an In-Home Exercise Program via Telerehabilitation: A Pilot Study of Lung Transplant Go (LTGO) - Choi, JiYeon; Hergenroeder, Andrea L.; Burke, Lora; Dabbs, Annette DeVito; Morrell, Matthew; Saptono, Andi; Parmanto, Bambang (International Journal of Telerehabilitation, 2016)
We evaluated the feasibility, safety, system usability, and intervention acceptability of Lung Transplant Go (LTGO), an 8-week in-home exercise intervention for lung transplant recipients using a telerehabilitation platform, and described changes in physical function and physical activity from baseline to post-intervention. The intervention was delivered to lung transplant recipients in their home via the Versatile and Integrated System for TeleRehabilitation (VISYTER). The intervention focused on aerobic and strengthening exercises tailored to baseline physical function. Participants improved walk distance (6-minute walk distance), balance (Berg Balance Scale), lower body strength (30-second chair stand test) and steps walked (SenseWear Armband®). No adverse events were reported. Participants rated the program highly positively in regard to the technology and intervention. The telerehabilitation exercise program was feasible, safe, and acceptable. Our findings provide preliminary support for the LTGO intervention to improve physical function and promote physical activity in lung transplant recipients.